Effects of smoking social cues on brand perception and smoking: an event-related potential study - Yiming Zhang; Zhan Wang; Fang Chen; Yuzhou Wang; Junyu Li (Frontiers in Psychiatry)
IntroductionSmokers’ dependence on tobacco products stems not only from substance addiction but also from social influences. While prior research has explored the impact of smoking action cues, it has largely overlooked smoking social cues and their role in shaping brand perception and smokers’ willingness to pay (WTP), leaving a gap in understanding their interaction. This study addresses the gap by analyzing event-related potentials (ERPs) and behavioral decisions in response to smoking social and action cues.MethodsUsing a 2×2 design (social cues: present vs. absent; action cues: present vs. absent), we assessed brand perception, WTP, and N1 and P3 ERP amplitudes in 22 smokers (18 males, mean age 23.14 ± 1.60 years).ResultsResults showed that smoking social cues increased brand perception and WTP while reducing N1 amplitudes, indicating that the presence of smoking social cues interfere with the processing of smoking action stimuli.DiscussionThese findings highlights the importance of avoiding the simultaneous inclusion of social and action cues in anti-smoking advertisements, which also provide valuable insights for smoking cessation research.